55.5k views
0 votes
2(x+3)=x-4 i really need help on this plss

1 Answer

2 votes

Answer:

X = -10

Explanation:


2(x + 3) = x - 4

Multiply each term in the parenthesis by 2


2 x + 6 = x - 4

Move variable to L.H.S and change its sign


2x - x + 6 = - 4

Move constant to R.H.S and change its sign


2x - x = - 4 - 6

Calculate


x = - 10

Hope this helps...

Good luck on your assignment...

User Sam Ginrich
by
6.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.